Association between parity and obesity patterns in a middle-aged and older Chinese population: a cross-sectional analysis in the Tongji-Dongfeng cohort study. Issue 1 (December 2016) - Li, Wending; Wang, Yi; Shen, Lijun; Song, Lulu; Li, Hui; Liu, Bingqing; Yuan, Jing; Wang, Youjie
Abstract Background Higher parity has been implicated as a risk factor for obesity of women. The objective of the study was to examine whether parity was associated with general obesity or abdominal obesity, or both, among middle-aged and older Chinese women. Methods A total of 12, 829 Chinese women (mean age: 64.8 years) with at least one live birth were selected from the Dongfeng–Tongji Cohort Study (phase II). We used body mass index to assess general obesity, and waist-to-hip ratio (WHR), waist-to-height ratio (WHtR) and waist circumference (WC) to assess abdominal obesity. We used multivariate linear and logistic regression models to investigate the association between parity and obesity. Results The values of all four obesity measures increased with the greater number of live births (P for trend <0.001). After adjustment for potential confounders, women with four or more children had 1.72 times (95 % confidence interval [CI], 1.41–2.10) higher risk of general obesity, and 1.93 (95 % CI, 1.57–2.37), 2.09 (95 % CI, 1.65–3.64) and 1.58 (95 % CI, 1.28–1.94) times risk of abdominal obesity assessed by WHR, WHtR and WC, respectively. Furthermore, we observed an ascending gradient between parity and the three abdominal obesity measures. Conclusions Parity was positively associated with risk of obesity, especially abdominal obesity, in the long term among Chinese women.